Ulcerative colitis mucosal transcriptomes reveal mitochondriopathy and personalized mechanisms underlying disease severity and treatment response - Yael Haberman (Nature Portfolio, 2019)
The severity of ulcerative colitis, and response to treatment, is highly variable. Here, the authors examine rectal gene expression signatures and faecal microbiomes of children and adults with the disease and provide new insights in to pathogenesis.